(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
Abstract: this article examines the expression of degree in adjectives in the Uzbek and English languages. It compares the morphological and syntactic means used to convey gradation of adjectives in these two languages. The analysis reveals both similarities and differences in the ways the degree of adjectives is marked. While both languages employ synthetic and analytic strategies, the specific morphemes and constructions utilized differ.